2008
DOI: 10.1017/s0317167100009525
|View full text |Cite
|
Sign up to set email alerts
|

Medication Use in Patients Presenting to a Rural and Remote Memory Clinic

Abstract: Cholinergic projection systems play a role in modulating cortical activity through activation of muscarinic receptors. Brain regions containing cholinergic neurons include the nucleus basalis of Meynert (NBM) and the medial septal nuclei (MSN), which send diffuse projections to cortex. 1-3 Brains of patients with Alzheimer's Disease (AD) exhibit loss of cholinergic neurons in the NBM and MSN. 4 These findings have lent considerable support to the cholinergic hypothesis of cognitive dysfunction.5 Acetylcholines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 22 publications
(16 reference statements)
0
15
0
Order By: Relevance
“…More detailed information about the clinic can be found in previous publications. [21][22][23][24][25][26][27][28][29][30][31] Data collected at the initial visit include: age, sex, years of formal education, MMSE score from the initial RRMC visit, CES-D depression scores, Self-Rating of Memory Scale, alcohol consumption, marital status, hours per week of work, past medical history, sleep concerns, possession of a driver's licence, and information on a family history of memory concerns. By the end of the day, patients are given a diagnosis as agreed upon by the assessment team.…”
Section: Methodsmentioning
confidence: 99%
“…More detailed information about the clinic can be found in previous publications. [21][22][23][24][25][26][27][28][29][30][31] Data collected at the initial visit include: age, sex, years of formal education, MMSE score from the initial RRMC visit, CES-D depression scores, Self-Rating of Memory Scale, alcohol consumption, marital status, hours per week of work, past medical history, sleep concerns, possession of a driver's licence, and information on a family history of memory concerns. By the end of the day, patients are given a diagnosis as agreed upon by the assessment team.…”
Section: Methodsmentioning
confidence: 99%
“…2,11 Medications considered anticholinergic included the American Geriatric Society's Updated Beer's Criteria and ranitidine in an effort to be consistent with Steve et al's paper and to form an accurate picture of trends over the 11-year period. 2,10 We additionally catalogued medications with central nervous system effects (benzodiazepines, hypnotics, non-anticholinergic antidepressants, antiepileptics, and lithium) and recorded each patient's total number of medications. 2,3,12,13 In an attempt to quantify polypharmacy, we totaled the number of medications at initial presentation.…”
Section: Methods and Analysismentioning
confidence: 99%
“…[7][8][9] In 2008, Steve et al analyzed the medication lists that 66 patients brought to their first visit at the RRMC. 10 The focus of that article was on the prevalence of polypharmacy, anticholinergic medication use, and benzodiazepine use. 10 They found that, at initial presentation, 24% of patients were taking an anticholinergic medication, 14% were taking a benzodiazepine, and the average number of medications per patient was 4.80 (standard deviation [SD], 3.66).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…19 More information on the RRMC is available elsewhere. [18][19][20][21][22][23][24][25][26][27][28] Decision-making is an increasingly important issue for patients with dementia. As the rates of dementia rise, more patients will experience irreversible cognitive incapacity and a loss of autonomy.…”
Section: Introductionmentioning
confidence: 99%